Approaches to interdisciplinary mixed methods research in land‐change science and environmental management. Issue 1 (30th December 2020) - Kinnebrew, Eva; Shoffner, Elizabeth; Farah‐Pérez, Aldo; Mills‐Novoa, Megan; Siegel, Katherine
Abstract: Combining qualitative and quantitative methods and data is crucial to understanding the complex dynamics and often interdisciplinary nature of conservation. Many conservation scientists use mixed methods, but there are a variety of mixed methods approaches, a lack of shared vocabulary, and few methodological frameworks. We reviewed articles from 2 conservation‐related fields that often incorporate qualitative and quantitative methods: land‐change science ( n = 16) and environmental management ( n = 16). We examined how authors of these studies approached mixed methods research by coding key methodological characteristics, including relationships between method objectives, extent of integration, iterative interactions between methods, and justification for use of mixed methods. Using these characteristics, we created a typology with the goal of improving understanding of how researchers studying land‐change science and environmental management approach interdisciplinary mixed methods research. We identified 5 types of mixed methods approaches, which we termed simple nested, informed nested, simple parallel, unidirectional synthesis, and bidirectional synthesis. Methods and data sources were often used to address different research questions within a project, and only around half of the reviewed papers methodologically integrated different forms of data. Most authors used one method to inform the other, rather than both informing one another. Very few articles used methodological iteration. Each methodological type has certain epistemological implications, such as the disciplinary reach of the research and the capacity for knowledge creation through the exchange of information between distinct methodologies. To exemplify a research design that can lead to multidimensional knowledge production, we provide a methodological framework that bidirectionally integrates and iterates qualitative and quantitative methods. Abstract : Article impact statement : Articles with mixed methods fit into 5 methodological types in which there is limited integration and iteration among methods. Abstract : Estrategias para la Investigación Interdisciplinaria con Métodos Mixtos en las Ciencias del Cambio de Suelo y el Manejo Ambiental Resumen: La combinación entre los métodos cualitativos y cuantitativos y los datos es crucial para el entendimiento de las dinámicas complejas y con frecuencia, de la naturaleza interdisciplinaria de la conservación. Muchos científicos de la conservación usan métodos mixtos, aunque existe una variedad de estrategias de métodos mixtos, una falta de vocabulario común y pocos marcos de trabajo metodológicos. Revisamos los artículos publicados en dos campos relacionados con la conservación, los cuales con frecuencia incorporan métodos cualitativos y cuantitativos: las ciencias del cambio de suelo ( n = 16) y el manejo ambiental ( n = 16). Examinamos cómo los autores de estos estudios abordaron la investigación de métodos mixtos al codificar las características metodológicas importantes, incluyendo las relaciones entre los objetivos de los métodos, la extensión de la integración, las interacciones iterativas entre los métodos y la justificación para el uso de los métodos mixtos. Con estas características creamos una tipología con el objetivo de mejorar el entendimiento de cómo los investigadores que estudian las ciencias del cambio de suelo y el manejo ambiental abordan la investigación interdisciplinaria de métodos mixtos. Identificamos cinco tipos de estrategias de métodos mixtos, que denominamos anidadas, anidadas informadas, paralelas simples, de síntesis unidireccional y de síntesis bidireccional. Con frecuencia se utilizaron métodos y fuentes de datos para responder a diferentes preguntas de investigación dentro de un proyecto y sólo alrededor de la mitad de los artículos revisados integraron de manera metodológica diferentes presentaciones de los datos. La mayoría de los autores usaron un método para orientar al otro método, en lugar de que ambos métodos se orientaran mutuamente. Fueron muy pocos los artículos que usaron la iteración metodológica. Cada estilo metodológico tiene ciertas implicaciones epistemológicas, como el alcance disciplinario de la investigación y la capacidad de creación de conocimiento por medio del intercambio de información entre las distintas metodologías. Proporcionamos un marco de trabajo metodológico que integre de manera bidireccional y reitere los métodos cualitativos y cuantitativos para ejemplificar un diseño de investigación que pueda derivar en la producción multidimensional del conocimiento.